2021
DOI: 10.2308/horizons-2020-147
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Accounting Research (ROAR) Scores: Ratings of Titles and Abstracts by Accounting Professionals

Abstract: The relevance of academic accounting research to practice has been frequently discussed in the accounting academy, yet very little data has been put forth in these discussions. We create Relevance of Accounting Research (ROAR) scores by asking accounting professionals to read and evaluate the titles and abstracts of every article published in 12 leading accounting journals for the years 2016 to 2018, inclusive. These scores allow for an evidence-based evaluation and discussion of how academic accounting resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…Indeed, while research assessment is increasingly based on quantitative metrics of citations, IF and journal rankings (Aistleitner et al , 2018), a growing number of voices are demanding a more holistic assessment of research (RQ+ Assessment Framework, the Declaration on Research Assessment (DORA), the Leiden Manifesto for research metrics, etc.). Accounting research is not exempt from these reflections (Burton et al , 2021a; Dechow et al , 2020), to the point where the question of its relevance is openly raised (Burton et al , 2021a). To fuel this debate, our study focuses on the quantitative indicators used to measure the impact of accounting research and on one particularly prolific accounting specialized area – environmental accounting.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, while research assessment is increasingly based on quantitative metrics of citations, IF and journal rankings (Aistleitner et al , 2018), a growing number of voices are demanding a more holistic assessment of research (RQ+ Assessment Framework, the Declaration on Research Assessment (DORA), the Leiden Manifesto for research metrics, etc.). Accounting research is not exempt from these reflections (Burton et al , 2021a; Dechow et al , 2020), to the point where the question of its relevance is openly raised (Burton et al , 2021a). To fuel this debate, our study focuses on the quantitative indicators used to measure the impact of accounting research and on one particularly prolific accounting specialized area – environmental accounting.…”
Section: Discussionmentioning
confidence: 99%
“…4. The “top 5” accounting journals are Accounting, Organizations and Society , Contemporary Accounting Research , Journal of Accounting and Economics , Journal of Accounting Research and The Accounting Review (Beets et al , 2015; Bonner et al , 2006; Burton et al , 2021a; Chan and Liano, 2009; Templeton and Lewis, 2015). …”
Section: Notesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fraser and Sheehy (2020) reported that more than half of practicing accountants never read articles published in academic journals. Burton, Summers, Wilks, and Wood (2022) asked 800 accounting practitioners whether, based on reading the abstracts of 1,254 articles published in 12 of the leading academic accounting journals from 2016 to 2018, they were interested in reading the full article. They found that about half of the articles were of interest to practitioners.…”
Section: Introductionmentioning
confidence: 99%